Hakikat Tuhan, Manusia, Masyarakat, Alam, dan Ilmu Pengetahuan serta Implikasinya dalam Pendidikan Islam - Nia nia rosita (SURAU : Journal of Islamic Education, 2025)
Abstrack Education is an important and fundamental pillar in the development of human civilization. However, the philosophical basis of education is often overlooked, even though a deep understanding of the nature of God, humans, society, nature, and science greatly determines the direction, objectives, and implementation of education. These five main elements are not only the objects of philosophical study, but also the foundation for building and shaping a holistic and transformative educational paradigm. This research is a literature study aimed at gaining a deep understanding of an issue by utilizing references or written sources as a basis for analysis. Islamic education must be based on a philosophical understanding of five important aspects, namely the nature of God as the main paradigm, humans as subjects and objects, society, nature, and science as means to achieve educational goals. These five elements are interrelated and form the basis for building an integral and transformative Islamic education system. The implication of examining these five main elements is that the design of the concept, implementation, and goals of education can be achieved optimally in accordance with Islamic expectations.   Abstrak Pendidikan merupakan pilar penting dan fundamental dalam perkembangan peradaban manusia. Namun, dasar filosofis pendidikan sering diabaikan, padahal pemahaman yang mendalam tentang sifat Tuhan, manusia, masyarakat, alam, dan ilmu pengetahuan sangat menentukan arah, tujuan, dan implementasi pendidikan. Kelima unsur utama ini tidak hanya menjadi objek studi filosofis, tetapi juga landasan untuk membangun dan membentuk paradigma pendidikan yang holistik dan transformatif. Penelitian ini merupakan studi literatur yang bertujuan untuk memperoleh pemahaman mendalam tentang suatu isu dengan memanfaatkan referensi atau sumber tertulis sebagai dasar analisis. Pendidikan Islam harus didasarkan pada pemahaman filosofis lima aspek penting, yaitu sifat Tuhan sebagai paradigma utama, manusia sebagai subjek dan objek, masyarakat, alam, dan ilmu pengetahuan sebagai sarana untuk mencapai tujuan pendidikan. Kelima elemen ini saling terkait dan membentuk dasar untuk membangun sistem pendidikan Islam yang integral dan transformatif. Implikasi dari mengkaji kelima elemen utama ini adalah bahwa desain konsep, implementasi, dan tujuan pendidikan dapat dicapai secara optimal sesuai dengan harapan Islam.